From Reflection to Action: Empowering Islamic Religious Education Teachers Through Structured Clinical Supervision - Nur Habibullah; Heru Setiawan; Muchtar Luthfi; Arwansyah bin Kirin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to develop and validate a needs-based clinical academic supervision model for Islamic Religious Education teachers at the secondary school level. The research approach used was qualitative, with data collected through interviews, focus group discussions, and document analysis. The results indicate that teachers' primary needs include active learning, classroom management, authentic assessment, and dialogic feedback. The developed model consists of three main components: needs analysis, collaborative supervision, and structured reflection. Expert validation scores indicated high feasibility of this model, with relevance (4.55), consistency (4.45), practicality (4.35), and potential effectiveness (4.45) all rated high. This study presents a framework for differentiated and dialogic supervision that integrates teacher needs analysis into clinical supervision and recommends its implementation to strengthen teachers' ongoing professional development and improve teaching quality. Implementation of this model is expected to increase supervision effectiveness, strengthen teachers' professional competencies, encourage innovative learning practices, and provide a policy basis for developing teacher training programs. Furthermore, this model can serve as a reference for further research evaluating the impact of needs-based supervision in various educational contexts.